Analisis Kesulitan Belajar Matematika pada Materi Jarak, Waktu, dan Kecepatan di Kelas 5 SD - Unaenah, Een; Nuraeni, Eni; Asmoro, Shifa Nur (Lembaga Yasin AlSys, 2023)
This study attempts to discover whether primary school students who are learning mathematics can solve issues involving distance, time, and speed and comprehend the solution, also whether there are any difficulties they encounter. Quantitative Descriptive research is this kind of study. This study aims to test students' knowledge of speed, distance, and time. It also conducts an interview with the instructor. Analyzing, interviews, tests, and documentation are among the ways used to acquire data. As for the descriptive methodology used in this study. The results of the student workmanship test were used to gather information about the challenges students encountered when solving math problems involving distance, time, and speed. The test's difficulty was a sign of students' lack of comprehension of the concepts of distance, time, and speed. Regarding the requirements for teacher interviews. The goal of interviewing teachers is to understand more about mathematics learning activities including distance, time, and speed as well as common errors made by pupils while attempting to solve problems using these concepts. According to the study's findings, arithmetic proficiency in the areas of time, distance, and speed in grade 5 SD is 80.06% in average, placing it in the